Market Segmentation Analysis Based on Demographic and Psychographic Factors of Potential Customers in The Sucean Bag Business - Amanda, Fistarika Della; Nurmasari, Nuraini Desty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
In the era of globalization and increasingly fierce business competition, a deep understanding of market segmentation is a key element in designing effective marketing strategies. This study delves into how demographic and psychographic factors of potential customers can be leveraged to enhance the competitive edge of the SUCEAN bag business. Utilizing quantitative methods and cluster analysis, this research aims to identify customer characteristics that can serve as a basis for grouping homogeneous market segments. This is expected to aid SUCEAN in formulating more targeted and effective marketing strategies, thereby increasing sales and overall business growth. The research findings reveal significant differences in consumer preferences and behaviors based on demographic variables such as age, gender, education, and income. Meanwhile, psychographic factors like lifestyle, personal values, and personality also play a crucial role in purchasing decisions. By understanding the combination of these factors, SUCEAN can develop more efficient and effective marketing strategies. These strategies include selecting appropriate promotional media, offering products that meet the needs and desires of specific market segments, and developing marketing campaigns that resonate with customer values.